Virtual Frisch grid perovskite CsPbBr3 semiconductor with 2.2-centimeter thickness for high energy resolution gamma-ray spectrometer - Qin, Haoming; Xiao, Bao; He, Xuchang; Ouyang, Xiao; Gao, Tingting; Wang, Yuquan; Wang, Luyao; Sun, Qihao; Shen, Nannan; Ouyang, Xiaoping; He, Yihui (Nature communications, 2025)
High intrinsic detection efficiency is as decisive as high energy resolution. Scaling up detector volume has presented great challenges, preventing perovskite semiconductors from reaching sufficient detection efficiency. We report a hole-only virtual-Frisch-grid CsPbBr 3 detector up to 2.2 cm thick for efficient gamma-ray spectroscopy. By utilizing high-quality columnar CsPbBr 3 single crystals up to ~1 cm 3 , we configure virtual-Frisch-grid detectors with optimized weighting potential distribution. These centimeter-thick detectors outperform ambipolar planar configuration, achieving a champion energy resolution of 1.9% at 662 keV. Time-of-flight analysis, stimulated by single gamma-ray photon, reveals hole carrier multiplication effect possibly caused by Auger recombination and space charge accumulation effect, collectively driving an anomalous stabilization process. Digital pulse measurements reduce the ballistic deficit, thereby improving the spectral response to 2.2% at 662 keV for 2.2 cm thick detector. The low-cost device fabrication and adequate detection efficiency of virtual-Frisch-grid detectors will surely foster the development of large-volume perovskite detectors. Qin et al. report single crystalline columnar CsPbBr3 with thickness up to 2.2 cm in a hole-only virtual Frisch grid configuration for gamma-ray detector with energy resolution of 1.9% at 662 keV. Time-of-light measurement reveals hole multiplication due to the defect-assisted Auger recombination.